2015
DOI: 10.1097/iae.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pars Plana Vitrectomy and Pars Plana Baerveldt Tube Placement in Eyes With Neovascular Glaucoma

Abstract: Combined pars plana vitrectomy and Baerveldt glaucoma shunt may be a useful procedure in reducing IOP and number of glaucoma medications in eyes with neovascular glaucoma along with stabilizing visual acuity in a majority of these eyes. Further studies are warranted to verify and expand on these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…We excluded cases where AIT is contraindicated, notably active neovascular glaucoma. This could bias the results toward AIT by excluding the most complex cases of glaucoma where IOP reduction with AIT (but not BGI) [21] might not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded cases where AIT is contraindicated, notably active neovascular glaucoma. This could bias the results toward AIT by excluding the most complex cases of glaucoma where IOP reduction with AIT (but not BGI) [21] might not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to the results of Kolomeyer et al . [ 30 ] They performed combined PPV and Baerveldt tube insertion procedure in eyes with NVG. Their results showed that logMAR visual acuities at 18-, 24-, 36-, and 48-month follow-up time points were significantly better than preoperative vision ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A significant IOP decrease was achieved with the procedure while visual acuity remained unchanged. However, it is important to note that 38 % experienced a decrease in vision [89] However, prospective and comparative studies with longer follow-up are still needed.…”
Section: Introductionmentioning
confidence: 99%